Expanded Territory: Marcus Vinicius on Pólvora Island, Espírito Santo - Marotto, Rafael Gonçalves; Cirillo, José (Farol, 2025)
This text investigates the artistic journey of Espírito Santo-born performer Marcus Vinicius de Souza Santos (1985-2012), particularly his work on Pólvora Island, located in Vitória, Espírito Santo. The works, titled "Expanded Territory I" and "Expanded Territory II," were part of and formed the basis for his final project during his Visual Arts degree at UFES in 2007. We will seek to identify how his body and plot are constructed as the material of his work, in a process that becomes a work. Using a basic methodological approach and a bibliographical-documentary investigative procedure, centered on Cecília Salles's Critical Methods of Creative Process, this text examines some aspects of the creative mind, highlighting tendencies and intentions of her poetic project.
Keywords: Ilha da Pólvora; Marcus Vinicius; expanded territory